Dampak Pembangunan Irigasi dalam Meningkatkan Pendapatan Petani Padi dalam Perspektif Ekonomi Islam (Studi Kasus Jorong Limo Suku Nagari Sungai Pua) - Arfin, Aila Rosalinda; Rahmi, Rahmi (ARZUSIN, 2026)
Irrigation development and the increase in rice farmers’ income have received attention in several studies, yet research that specifically discusses the impact of irrigation development on increasing farmers’ income based on differences in water distribution among upstream, middle, and downstream areas from the perspective of Islamic economics remains limited. This study aims to analyze the impact of irrigation development in increasing the income of rice farmers in Jorong Limo Suku, Nagari Sungai Pua, from the perspective of Islamic economics. This study used a qualitative approach with a case study design, involving rice farmers, the jorong head, and irrigation managers selected through purposive sampling. Data were collected through semi-structured interviews, observation, and documentation, and were then analyzed using the interactive analysis model of Miles and Huberman through the stages of data reduction, data display, and conclusion drawing. The results show that irrigation development has had an impact on increasing crop yields and the income of some rice farmers, particularly in upstream and middle areas that have better access to water. However, farmers in downstream areas have not experienced a significant increase in income because water distribution remains uneven. This finding contributes to the development of agricultural development studies and Islamic economics, particularly regarding the principles of equitable distribution of water resources and public welfare. The conclusion of this study emphasizes that equitable water distribution and fair irrigation management are important factors in improving farmers’ welfare sustainably. The practical implications of this study indicate the need to improve irrigation governance by the government and irrigation managers so that water distribution becomes more effective, equitable, and aligned with the principle of justice in Islamic economics.